The Light of Knowledge Literacy Activism and the Politics of Writing in South India - Cody, Francis (Expertise: Cultures and Technologies of Knowledge, 2013)
Cowinner of the Society for Linguistic Anthropology's Edward Sapir Book PrizeSince the early 1990s hundreds of thousands of Tamil villagers in southern India have participated in literacy lessons and other events designed to transform them into active citizens with access to state power. These efforts are part of a movement known as the Arivoli Iyakkam (the Enlightenment Movement), one of the most successful mass literacy movements in recent history. This rich ethnographic account of highlights the paradoxes inherent in such movements that seek to emancipate people through literacy."A work of linguistic anthropology that makes crucial contributions to the study of literacy and language ideologies. It is also a broadly ranging work of social theory that will be of interest to students and scholars of the postcolonial state and neoliberal governmentality in South Asia and beyond, and of activism and social movements more generally."-Anthropological Quarterly